Pythium insidiosum Thai isolates: Molecular phylogenetic analysis - Angkana Chaiprasert (2018)
Background: Pythium insidiosum is an oomycete that infects both humans and animals, leading to a lifethreatening infectious disease called "pythiosis". Animal pythiosis presents with lesions of the skin, gastrointestinal tract, lung and bone, whereas human pythiosis presents with two common clinical forms, vascular pythiosis involving arteries, and ocular pythiosis involving the eye. Pythiosis in humans has been reported exclusively from Thailand. The disease in animals has been found around the world, but its occurrence has never been reported from Thailand. Objective: To group P. insidiosum based on molecular phylogenetic analysis, investigating correlation between phylogenetic group, geographic distribution, and host specificity of this pathogen. Methods: 113 rDNA internal transcribed spacer sequences of P. insidiosum were also obtained for phylogenetic analyses. These included 32 human isolates and 59 environmental isolates from Thailand, and four additional human isolates and 18 animal isolates from around the world. Results: P. insidiosum existed in three distinct clades in accordance with geographic distribution; clade-I contained American isolates, clade-II contained Asian and Australian isolates, and clade-III contained mainly Thai isolates. The Thai isolates existed only in clade-II and clade-III. Conclusion: There were two major subpopulations of P. insidiosum in Thailand. There were no correlation between the two Thai subpopulations of P. insidiosum and geographic regions or host specificity.